2020
DOI: 10.2196/14629
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Upper Extremity Rehabilitation by Combining Telerehabilitation With an Exergame in People With Chronic Stroke: Protocol for a Mixed Methods Study

Abstract: Background Exergames have the potential to provide an accessible, remote approach for poststroke upper extremity (UE) rehabilitation. However, the use of exergames without any follow-up by a health professional could lead to compensatory movements during the exercises, inadequate choice of difficulty level, exercises not being completed, and lack of motivation to pursue exercise programs, thereby decreasing their benefits. Combining telerehabilitation with exergames could allow continuous adjustmen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…In particular, these apparent benefits of VR technologies open new perspectives and opportunities for tele-rehabilitation, an emerging solution which allows patients to have access to a home-based therapy following discharge from the stroke and rehabilitation units and to extend patients' therapy duration, with remote monitoring from therapists (Allegue et al, 2020;Laver et al, 2020). Self-administered treatment at home, through technology-based training and conventional exercises, has been previously found to be accepted by chronic stroke patients (Nijenhuis et al, 2017).…”
Section: Benefits Of Integrating Virtual Reality As a Therapy Tool For Therapistsmentioning
confidence: 99%
“…In particular, these apparent benefits of VR technologies open new perspectives and opportunities for tele-rehabilitation, an emerging solution which allows patients to have access to a home-based therapy following discharge from the stroke and rehabilitation units and to extend patients' therapy duration, with remote monitoring from therapists (Allegue et al, 2020;Laver et al, 2020). Self-administered treatment at home, through technology-based training and conventional exercises, has been previously found to be accepted by chronic stroke patients (Nijenhuis et al, 2017).…”
Section: Benefits Of Integrating Virtual Reality As a Therapy Tool For Therapistsmentioning
confidence: 99%
“…Of these, the full texts of 159 studies were screened for inclusion. This review included 31 studies [ 19 49 ] and ten protocols of ongoing studies [ 50 59 ], adding eleven studies and five protocols to the recent Cochrane review [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…All interventions include a combination of intervention components, such as computer game-based therapy reviewed via videoconference [ 50 , 55 ] or telephone [ 58 ]. Other intervention components that will be used in combination with video or telephone review, such as activity monitors used only by participants to self-monitor their physical activity [ 52 , 57 ] or upper limb movement [ 55 ], and access to online or smartphone-enabled educational content [ 53 , 59 ], were not reported on here, as they will not be reviewed remotely by the clinician.…”
Section: Resultsmentioning
confidence: 99%
“…The rehabilitation of upper limb functionality with virtual reality has been explored mainly in people with stroke [69,70] or multiple sclerosis [71,72]. Our analysis showed that exergaming can also be used to train upper limb mobility below and above the shoulder girdle, improving the overall functional range of elderly people.…”
Section: Discussionmentioning
confidence: 99%